The chemistry of amine radical cations produced by visible light photoredox catalysis - Hu, Jie; Wang, Jiang; Nguyen, Theresa H.; Zheng, Nan (Beilstein Journal of Organic Chemistry, 2013)
Amine radical cations are highly useful reactive intermediates in amine synthesis. They have displayed several modes of reactivity leading to some highly sought-after synthetic intermediates including iminium ions, α-amino radicals, and distonic ions. One appealing method to access amine radical cations is through one-electron oxidation of the corresponding amines under visible light photoredox conditions. This approach and subsequent chemistries are emerging as a powerful tool in amine synthesis. This article reviews synthetic applications of amine radical cations produced by visible light photocatalysis.
Keywords: α-amino radical; amine radical cation; catalysis; distonic ion; free radical; iminium ion; photoredox; visible light